An efficient clocking scheme for quantum-dot cellular automata. Issue 1 (2nd January 2020) - Goswami, Mrinal; Mondal, Anindan; Mahalat, Mahabub Hasan; Sen, Bibhash; Sikdar, Biplab K.
ABSTRACT: Fast pace growth in the IC industry is facing the challenges of feature size reduction which in turn demands an alternative to current CMOS VLSI. Quantum-dot cellular automata are emerging as one of the viable alternative nanotechnologies with high device density, high operating frequency and low power characteristics. Information transition and propagation in QCA take place with the underlying clocking circuitry. Thus, clocking is the main source of power of the QCA circuit as well as play the vital role of information synchronisation in QCA circuit. For efficient design and to provide routing option, a regular, scalable clocking structure becomes the utmost necessity of QCA circuit. In this context, a robust, efficient and scalable (RES) clocking scheme for QCA circuit is proposed which can facilitate three directional information flow within a single clock zone. Also, it can facilitate the feedback path without extra layer (unlike 2DDwave scheme) and overcome the complex multilayer wire crossing (unlike USE scheme) with most promising coplanar crossover. Simulation results underpin the significant improvement in terms of clocking zone, area and cells.